Bioprocessing of wheat (Triticum aestivum cv. Kronstad) bran from Northwest Mexico: effects on ferulic acid bioaccessibility in breads - María Fernanda Amaya Villalva; Gustavo González-Aguilar; Ofelia Rouzaud Sández; Humberto Astiazarán García; Ana Irene Ledesma Osuna; Guadalupe Amanda López-Ahumada; Rosario Maribel Robles-Sánchez (CyTA - Journal of Food, 2018)
Evaluating the biological potential of wheat grain cultivated in northwestern Mexico is important because it mainly varies according to the cultivar and production area. The aim of the present study was to evaluate ferulic acid (FA) bioaccessibility in breads supplemented with bioprocessed bran. Bran that was bioprocessed with xylanase enzyme (EB), yeast fermentation (FB), and a combination of both treatments (FEB) showed a higher total phenol content and antioxidant capacity compared with native bran (NB), and the majority of these components were found in a bound fraction. For NB and bioprocessed bran, FA was found at higher levels compared to the other hydroxycinnamic acids evaluated. Bioprocessing increased the free FA content six-fold compared to NB. The % bioaccessibility of FA in different breads increased in the following order: FEB<NB<FB<EB. The addition of bioprocessed bran is may be the simple way to increase the amount of bioactive compounds in a bread product.